Disaster Communications in a Changing Media World. - Haddow, George D. (Elsevier Science, 2013)
Communications are key to the success of disaster mitigation, preparedness, response, and recovery. Accurate information disseminated to the general public, to elected officials and community leaders, as well as to the media, reduces risk, saves lives and property, and speeds recovery. Disaster Communications in a Changing Media World, Second Edition, provides valuable information for navigating these priorities in the age of evolving media. The emergence of new media like the Internet, email, blogs, text messaging, cell phone photos, and the increasing influence of first informers are redefi.